Study on the effect of different arrival patterns on an emergency department's capacity using discrete event simulation - Joshi, Amita J. (Kansas State University, 2008)
Emergency department (ED) overcrowding is a nationwide problem affecting the safety and preparedness of our health care system. Many hospital EDs face significant short and intense surges in demand on a daily basis. However, the surge in demand during disaster event is not short and intense, but it is a sustained one. In order to meet this sudden surge as defined above, hospital EDs need to be more prepared and efficient to cater to increased volume of demand involving huge uncertainties. This thesis looks at the creation and use of discrete event simulation modeling using ARENA 10.0 software. In this thesis, an attempt is made to show how the different arrival patterns and time durations for which victims keep arriving affect the EDs ability to treat the patients. It is shown, how the model can be used to estimate additional resources that would be required to accommodate additional patients within the ED. Various shapes of arrival distributions were tested for different time durations. It was found that the arrival distribution with parameters (3, 4), (3, 3), (4, 2) and (2, 4) did not challenge the institutional capacity. In other words, the hospital was able to treat all the patients without compromising the quality of care up to 24 hours. However, distribution with parameter (3, 2), (2, 2), (3, 1), (1, 2), (2, 3), (2, 1), (1, 4), (1, 3), (1, 1) and (0.5, 2) did affect the system performance. Under these distributions, there was at least one patient who was either dead, LWBS or diverted. This indicates the immediacy with which victims arriving under these distributions overwhelmed the limited resources Our aim was to study, how many more resources would the ED need in order to have zero critical expire, zero Left without Being Seen (LWBS) and zero patients diverted. Arrival distribution (1, 2) was randomly selected to study this objective and it was found that for a 24 hours of simulation run time, an additional of two full trauma resources were required in order to have zero critical expire in trauma rooms area and additional of five ED beds and three nurses were required in treatment area for patients with moderate severity to have zero LWBS. With these additional resources, the ED was also able to treat all the non disaster related patients thereby having zero patients diverted. The same procedure can be used to determine the number of additional resources ED would require to treat all the victims arriving with the rest of the arrival distribution for different time periods. The simulation model built would help the emergency planners to better allocate and utilize the limited ED resources in order to treat maximum possible patients. It also helps estimate the number of additional resources that would be required in a particular scenario.
Keywords: Simulation; Mass Casualty; Emergency department; Arrival patterns; Terrorist bombing; Capacity; Arena; Health Sciences, Health Care Management (0769)